The Egyptian Background of Gnostic Mythology - Gaston, Thomas (Numen, 2015)
The mythologies recorded by Irenaeus that he ascribes to the Gnostics contain many features that are difficult to explain by reference solely to Jewish sources, whether orthodox or heterodox. Previously, Douglas Parrott proposed an Egyptian background for the pattern of divinities found in the Gnostic text Eugnostos. In this article, it is argued that the so-called Ophite mythology recorded by Irenaeus is earlier than Eugnostos and has more compelling parallels with Egyptian theogony. An Egyptian background for the Barbeloite mythology is also speculated. These parallels demonstrate that there is scope for further research into the Egyptian origins of Gnosticism.